'Now My Life in Syria Is Finished': Case Studies on Religious Identity and Sectarianism in Narratives of Syrian Christian Refugees in Austria. Issue 4 (1st October 2016) - Schmoller, Andreas
ABSTRACT: Using semi-structured life story interviews with Syrian Christian refugees in Austria, this article investigates the impact on identity of the conflict in Syria and the resulting act of seeking refuge outside Syria. It suggests that the sectarian dynamics of the war affect religious minorities in particular, and the method of using biographical case studies allows an analysis of how the sectarianization discourse is used by interviewees to construct their autobiographical narratives of life as refugees. The results, taken from four case studies, show that in each case, religion is a strong marker, providing a framework for self-interpretation in a period of change and/or disruption. In most cases, post-flight identity as a matter of 'translocational' positioning is constructed within the framework of sectarianism. The argument of the article is twofold: first, sectarianism provides a setting for Syrian Christians that is appropriated through diverse biographical patterns. Second, sectarianism as a narrative strategy is modelled by and responds to contexts in the host society. The results of this study aim to offer important suggestions for understanding the particular experience of Christian refugees settling in the European diaspora.